Capsular closure outweighs head size in preventing dislocation following revision total hip arthroplasty. Issue 2 (March 2020) - Pedneault, Christopher; Tanzer, Dylan; Nooh, Anas; Smith, Karen; Tanzer, Michael
Introduction: The high dislocation rate following revision total hip arthroplasty (THA) has been shown to be significantly reduced by closing the posterior capsule and by the use of large diameter femoral heads. The relative importance of each of these strategies on the rate of dislocation remains unknown. We undertook a study to determine if increasing femoral head diameter, in addition to posterior capsular closure would influence the dislocation rate following revision THA. Methods: We retrospectively reviewed 144 patients who underwent a revision THA. We included all patients who underwent revision THA with closure of the posterior capsule and who had at least a 2-year minimum follow-up. 48 patients had a 28-mm femoral head, 47 had a 32-mm head and 49 patients had a 36-mm femoral head. Results: At a minimum follow-up of 2 years, there were 3 dislocations. There were no dislocations in the 28-mm group (0%), 2 in the 32-mm group (4%) and 1 in the 36-mm group (2%). Head size alone was not found to significantly decrease the risk of dislocation (28-mm versus 32-mm p = 0.12; 28-mm versus 36-mm p = 0.27; 32-mm versus 36-mm p = 0.40). Conclusion: Both large diameter heads and careful attention to surgical technique with posterior capsular closure can decrease the historically high dislocation rate after revision THA when utilising the posterolateral approach. Capsular closure outweighs the effect of femoral head diameter in preventing dislocation following revision THA through a posterolateral approach.